Intellectual property perspectives on the regulation of new technologies - Pistorius, Tana; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
Intellectual Property Perspectives on the Regulation of New Technologies explores the challenges that emerging technologies and technology-driven practices pose for traditional notions of intellectual property (IP) law and policy. This book exposes the intimate relationship between IP and technology and demonstrates how most substantial revisions to IP law have been driven by technological innovations. Authors offer perspectives from across the intellectual property law spectrum and address questions such as: is the law evolving in the right direction?; and is the regulation of emerging technologies supported by sound policy objectives? The resulting discussion exposes the disparate manner in which IP law has responded to challenges posed by innovation and new technologies. In Part I authors explore whether the regulation of new technologies has fundamentally altered the object and purpose of IP law, including the balance of interests. Part II focuses on the impact of digital technologies, specifically on copyright law and policy. Covering a diverse range of topics, this book will be of interest to scholars who are researching the relationship between technological development and IP law and practice. It will also be a useful resource for those who have an interest in the evolving nature of IP law.
Introduction: Tana Pistorius -- Part I Impact of new technologies across IP -- 1. What is the role of new technologies in tensions in Intellectual Property? / Margaret Ann Wilkinson -- 2. Caveats of intermediary liability in the Domain Name System: a review of the ICANN new gTLD right protection measures / Hong Xue -- 3. Patentability of human enhancement: from ethical dilemmas to legal (un)certainty / Ana Nordberg -- 4. Patent claim interpretation and new technologies: re-thinking the problem/solution approach / Milton Lucídio Leão Barcellos -- Part II Technological developments and copyright -- 5. Asking the right questions in copyright cases: lessons from Aereo and its international brethren / Rebecca Giblin and Jane C. Ginsburg -- 6. Contemporary challenges to the territorial nature of copyright / Johan Axhamn -- 7. 'Browsing', 'Linking' and 'Framing' in the light of the EU Court of Justice's (CJEU) case law / Irini Stamatoudi -- 8. The liability of intermediaries for online copyright infringement in the EU: new evolutions / Tatiana-Eleni Synodinou -- 9. The argument for "non-consumptive use" in the EU: how copyright could be redefined to allow text and data mining / Paweł Kamocki -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: právo duševního vlastnictví; duševní vlastnictví; technologie; intellectual property law; intellectual property; technology; e-knihy online; e-books online